0226 Sense Of Fairness Alters After Sleep Loss: A Preliminary Research. (27th April 2018) - Mai, Z; Zhou, J; Lin, Y; Fu, Y; Hu, P; Zhou, X; Ma, N
Abstract: Introduction: The effects of sleep deprivation (SD) on decision-making are particularly complex, and the results of the relative previous studies were inconsistent. In the present study, we applied a modified Ultimatum Game to investigate the potential mechanism of the effect of sleep deprivation on sense of fairness. Methods: Fifteen college students (8 males, age: 21.53 ± 2.00 years) underwent a night of normal rested sleep (NS) and a 24-hour monitored sleep deprivation (SD) in a repeated measures design. Light was controlled to <50 lux and temperature was 25 °C. Participants were asked to complete an Ultimatum Game, which participants play as responder to decide whether reject the money (from 0 ¥ to 10 ¥) from the virtual proposer who allocated 10 ¥ between the responder and themselves. We divided the proposing splits into 5 groups, extremely unequal splits (0:10, 1:9), moderate unequal split (3:7), relatively equal splits (4:6, 5:5, 6:4), moderate beneficial split (7:3), and extremely beneficial splits (9:1, 10:0). A repeated measures ANOVAs and several paired t tests were used in present study to compare the rejection rates of responders. Results: The repeated measures ANOVAs of 5 (splits) × 2 (state: NS/SD) showed significant main effects of splits (F=19.963, p<0.001) and state (F=8.718, p=0.01) with no significant interaction, which indicated that people prefer the more beneficial splits and SD would increase the probability of rejection. Further t-test analysis found that rejection happened more after SD in the moderate unequal and beneficial splits conditions (p=0.029, p=0.045). Conclusion: The findings in the present study indicate that people after sleep loss will show lower tolerance for moderate unequal splits, irrespective of the benefit of the splits. SD selectively alters individual's sense of fairness, particularly in the moderate intensity of fairness. Support (If Any): National Natural Science Foundation of China 31500906, 31671165 and National Basic Research Program of China (973 Program: 2015CB856400).